THE ROLE OF GREEN HUMAN RESOURCE MANAGEMENT IN PROMOTING SUSTAINABLE MANUFACTURING PRACTICES: AN ANALYTICAL STUDY IN INDUSTRIAL ORGANIZATIONS IN NAJAF ASHRAF - Mundher Abbas Shaalan (Scholars Digest Publishing, 2024)
The main purpose of this research is to study the role of green human resource management in achieving sustainable manufacturing practices in industrial organizations in Najaf. The study question is the degree of practicing green human resource management in industrial organizations in Najaf. To determine the extent of the relationship and impact of green human resource on sustainable manufacturing practices in industrial organizations in Najaf The main and sub-hypotheses of the research were tested and the study used a sample of 40 individuals. working in industrial organizations in Najaf. Use the statistical program (SPSS) to analyze the data. The results showed that there is a correlation and impact between green human resource management and the variable of sustainable manufacturing, While the study recommended that the researched organizations should carry out employee competencies development processes based on environmental foundations, the study also recommended that human resource management in the organizations under study should develop indicators for green performance that are friendly to the environment to manage and evaluate performance.
Keywords: Green Performance Evaluation, Green recruitment, Sustainable Manufacturing.